The Writing Strategies used by Engineering ESL Malay Learners - Abdullah, Muhammad Ridhuan Tony Lim (International Journal of Arts & Sciences, 2009)
One of the most significant factors that affect the performance of learners with learning a second language is difficulty with written skill. This paper reveals a study conducted as a qualitative research to analyze the written product as well as writing strategies of four ESL Malay undergraduate engineering students of a local private university used while completing a writing task. Specifically the study aimed to address the following research questions : 1) What are the writing strategies used by four ESL Malay undergraduate engineering students when they write composition in English? 2) Are there any differences between the writing strategies used by good ESL students to those used by the weaker ones? Think-aloud protocols, written essays, post-session interviews and audiotapes were used to examine the writing processes and strategies of two groups of students, two students in each group of good and weak learners. The think-aloud and interview protocols were transcribed verbatim for analysis. Analyses of the findings revealed that the two groups of students shared common writing strategies mainly cognitive strategies to generate ideas for their essay. Metacognitive and Social strategies were also used to aid in generating of ideas and searching for correct words or expressions. The strategies were used in combination and in a recursive manner to attain certain goals in their writing. The difference in the strategy use between the two groups of good and weak students lies in the amount of strategies being used, reason for the use and how the students regulated the strategies to solve problems concerning the writing task.